Extended EEG and non‐convulsive status epilepticus: Benefit over routine EEG?. (27th December 2016) - Eskioglou, E.; Stähli, C.; Rossetti, A. O.; Novy, J.
Abstract : Objective: EEG monitoring is increasingly used in critically ill patients, but impact on clinical outcome remains unclear. We aimed to investigate the benefit of repeated extended EEG in the prognosis of patients with non‐convulsive status epilepticus (SE). Materials & Methods: We retrospectively collected 29 consecutive patients with non‐convulsive SE without coma, who underwent repeated extended EEG between 2013 and 2015. We compared these patients with an historical age‐matched group of 58 patients managed between 2011 and 2013 with routine EEG only. We excluded patients treated with therapeutic coma for SE treatment. Outcome at hospital discharge was categorized as return to baseline conditions, new disability, and death. Results: Severity of SE was similar in the two groups, with similar proportion of potential fatal etiologies (58% in the extended EEG group vs 60%, P =.529), similar STESS scores (median was three in both groups, P =.714), and comparable acute hospitalization duration (median of 15 vs 11 days, P =.131). The extended EEG group received slightly more anti‐epileptic drugs (median was three in both groups, P =.026). Distribution of the outcome categories at hospital discharge was similar ( P =.129). Conclusions: Extended EEG used for the management of non‐convulsive status epilepticus does not seem to improve clinical outcome, but is associated with a higher number of prescribed anti‐epileptic drugs. The benefit of continuous EEG monitoring in non‐convulsive SE without coma SE should be addressed through a randomized trial.